A CRITICAL STUDY OF REVELATION : (Comparative Study of Classical and Contemporary Muslim Scholarly Thought) - Alim, Khozinul (LP2M Institut Agama Islam Al-Qur'an Al-Ittifaqiah Indralaya, 2024)
The debate regarding the nature of revelation is a classic phenomenon that occurs especially among kalam scholars. In these debates, sometimes some try to find a middle way so as to find common ground (ikhtilāf tanawwu') so that the truth of an opinion does not mean blaming another opinion. However, sometimes there is no common ground (itkhtilaf taḍād) where an opinion cannot tolerate another opinion because it is contradictory and cannot be compromised. The author wishes to explain the etymology and terminology of revelation along with the process of revelation to the prophet. The author will also try to explain several expert views on the pronunciation and meaning of the Koran, along with the views of contemporary thinkers regarding the process of receiving revelation from the prophets. This research is included in the type of qualitative research, and the research data source perspective uses library research. Data collection techniques in this research include determining the problem, looking for verses related to al-Waḥy, exploring and comparing these verses with mu'tabar books, to extract common threads and analyzing the data using descriptive analysis as a way to resolve the problem, narrated and then analyzed using content analysis and linguistics. The results of this research explain the problems with the pronunciation of the Al-Qur'an; several scholars believe that the Al-Qur'an comes from Allah ﷻ both in terms of meaning and pronunciation. However, other opinions believe that the Qur'an is absolute and qaṭ'ī is only its meaning. Meanwhile, contemporary thinkers also have different opinions regarding the revelation of the Koran. Some tend to believe that revelation is obtained without effort. Some believe that the Prophet Muhammad ﷺ received revelations through his spiritual journey since childhood.